New master’s program «Technology of biopharmaceuticals». - V. I. Shvets; D. G. Pobedimskiy; G. I. Lapshenkov; D. I. Bairamashvili; A. K. Frolkova (Тонкие химические технологии)
Scientific and conceptual basis of the new Master’s program “Technology of biopharmaceuticals” has been proposed. The development is illustrated by the use of a general organizational approach, which provides training of scientific and technological brain-power in the field of technology of biopharmaceuticals. This approach consists in integration of the fundamental science represented by leading Russian academic and industrial centers of the medicinal and biological sphere and of the higher school.